SCIENTIFIC AND THEORETICAL FOUNDATIONS OF ENSURING FOOD SECURITY IN A COUNTRY - Mukhammadiyeva, Yulduz Yusupovna; Rustamova, Dildora Rustamova (THE INNOVATION ECONOMY, 2026)
This article analyzes the theoretical aspects of ensuring food safety, the problem of ensuring food safety and scientific theoretical views on ensuring food safety. At the same time, an author's definition of food safety was developed.